2020
DOI: 10.1155/2020/4062813
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mechanism of Iridoid Glycosides Derivatives from Fructus Gardeniae in Jiangxi Province by Network Pharmacology

Abstract: Objective. To investigate the pharmacological mechanism of the iridoid glycosides from Fructus Gardeniae in Jiangxi province by network pharmacology. To provide a valuable research strategy for the rational use and in-depth research and development of Fructus Gardeniae from Jiangxi. Method. Previous research results of our group show that the contents of iridoid glycosides in Fructus Gardeniae from Jiangxi province have a significant difference compared with other regions (P<0.05). Based on our previous exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Modern experimental studies have reported antioxidative properties of Gardeniae Fructus extract [7,8] and anti-inflammatory effects of Perillae Folium extract [9,10]. Minutely, Liu et al reported in 2020 that Gardeniae Fructus has diuretic, anti-inflammatory, and hemostatic effects; it also protects the liver and gallbladder from infringement and treats cardiovascular and cerebrovascular diseases [19] and its chemical composition includes iridoid glycosides (geniposide, gardenoside, etc.) [20], crocins [21], phenylpropanoids [22], glycoprotein [23], and polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Modern experimental studies have reported antioxidative properties of Gardeniae Fructus extract [7,8] and anti-inflammatory effects of Perillae Folium extract [9,10]. Minutely, Liu et al reported in 2020 that Gardeniae Fructus has diuretic, anti-inflammatory, and hemostatic effects; it also protects the liver and gallbladder from infringement and treats cardiovascular and cerebrovascular diseases [19] and its chemical composition includes iridoid glycosides (geniposide, gardenoside, etc.) [20], crocins [21], phenylpropanoids [22], glycoprotein [23], and polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…OB is a reliable indicator to evaluate the intrinsic quality of drugs objectively, which represents to the speed and degree of absorbing drugs into the circulatory system. And DL represents the sum of the pharmacokinetic properties and safety of compounds, which is calculated by comparing the functional or physical properties of the compounds with those of the majority of known drugs [ 20 ]. In this paper, the compound name “Leigongteng” was inputted to the TCMSP database, and active ingredients with DL ≥ 0.18 and OB ≥ 30% were selected for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…OB is a reliable indicator to evaluate the intrinsic quality of drugs objectively, which represents to the speed and degree of absorbing drugs into the circulatory system. And DL represents the sum of the pharmacokinetic properties and safety of compounds, which is calculated by comparing the functional or physical properties of compounds with those of the majority of known drugs [52]. In this paper, the compound name "leigongteng" was inputted to the TCMSP database and active ingredients with DL 0.18 and OB 30% were selected for subsequent analysis.…”
Section: Active Components Screeningmentioning
confidence: 99%